Long-term room temperature preservation of corpse soft tissue: an approach for tissue sample storage - Caputo, Mariela (BioMed Central, 2011)
BACKGROUND: Disaster victim identification (DVI) represents one of the most difficult challenges in forensic sciences, and subsequent DNA typing is essential. Collected samples for DNA-based human identification are usually stored at low temperature to halt the degradation processes of human remains. We have developed a simple and reliable procedure for soft tissue storage and preservation for DNA extraction. It ensures high quality DNA suitable for PCR-based DNA typing after at least 1 year of room temperature storage. METHODS: Fragments of human psoas muscle were exposed to three different environmental conditions for diverse time periods at room temperature. Storage conditions included: (a) a preserving medium consisting of solid sodium chloride (salt), (b) no additional substances and (c) garden soil. DNA was extracted with proteinase K/SDS followed by organic solvent treatment and concentration by centrifugal filter devices. Quantification was carried out by real-time PCR using commercial kits. Short tandem repeat (STR) typing profiles were analysed with 'expert software'. RESULTS: DNA quantities recovered from samples stored in salt were similar up to the complete storage time and underscored the effectiveness of the preservation method. It was possible to reliably and accurately type different genetic systems including autosomal STRs and mitochondrial and Y-chromosome haplogroups. Autosomal STR typing quality was evaluated by expert software, denoting high quality profiles from DNA samples obtained from corpse tissue stored in salt for up to 365 days. CONCLUSIONS: The procedure proposed herein is a cost efficient alternative for storage of human remains in challenging environmental areas, such as mass disaster locations, mass graves and exhumations. This technique should be considered as an additional method for sample storage when preservation of DNA integrity is required for PCR-based DNA typing.